Books Without Borders, Volume 1 - Fraser, Robert. author. aut Link
XV, 210 p. 14 illus.
Keywords: Where does the book belong? Does it enshrine the soul of a nation, or is it a means by which nations talk to one another, sharing ideas, technologies, texts? This book, the first in a two-volume set of original essays, responds to these questions with archive-based case studies of print culture in a number of countries around the world.